The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6ra17946k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of mild oxidized graphene with O-phenylenediamine for highly thermally conductive and thermally stable epoxy composites

Abstract: In this study, an effective and novel method was developed to improve the thermal conductivity of epoxy composites by functionalization of graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…6C shows pitting initiation healing by the alkyl amine-functionalized GO on the Mg alloys. [47][48][49][50] Furthermore, the elemental compositions suggested that the oxygen concentration was less, as compared with the traditional epoxy-coated Mg alloys. From the microstructure, we concluded that the octylamine-functionalized GO materials have signicant corrosion resistance in a 3.5% NaCl solution.…”
Section: Afm Alloy Microstructurementioning
confidence: 99%
“…6C shows pitting initiation healing by the alkyl amine-functionalized GO on the Mg alloys. [47][48][49][50] Furthermore, the elemental compositions suggested that the oxygen concentration was less, as compared with the traditional epoxy-coated Mg alloys. From the microstructure, we concluded that the octylamine-functionalized GO materials have signicant corrosion resistance in a 3.5% NaCl solution.…”
Section: Afm Alloy Microstructurementioning
confidence: 99%
“…This enhancement is due to the improved compatibility of functionalized sisal with epoxy matrix. 10 To evaluate the thermal stability of the epoxy composite, the kinetic analysis of thermal stability has been investigated. 60,61 Doyle’s model is used to calculate the decomposition temperature of neat epoxy and its composites.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports showed that the introduction of functional moieties on the surface of the fiber enhances the interface between fibers and matrix. 10 The functionalization of the fibers is vital to improving the interfacial bond between matrix and fiber, and it also enhances the properties of composite materials. Various methods have been reported for surface modification including chemical, 11 physical, 12 and biological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…By adding just 6 wt. % of OPD-f-Graphene 13 fold of rise in thermal conductivity has been noted [24]. The thermal conductivity of polyimdie lled boron nitride is improved to 1.2 W.m -1 .K -1 after surface modi cation of boron nitride particles [25].…”
Section: Introductionmentioning
confidence: 97%